2002
DOI: 10.1530/eje.0.1470201
|View full text |Cite
|
Sign up to set email alerts
|

Sequential ACTH and catecholamine secretion in a phaeochromocytoma

Abstract: Objective: We describe a patient with an ACTH-producing phaeochromocytoma who initially presented with hypercortisolism and normal catecholamine concentrations, followed by near-normalisation of ACTH secretion and massive catecholamine secretion. In vitro studies were carried out on the tumour to evaluate the interaction between the tumour cells and normal adrenal cortex. Methods and Results: A 30-year-old man initially presented with severe hypercortisolism, biochemical evidence of ectopic ACTH production, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
1
12
1
Order By: Relevance
“…Literature review revealed 61 papers and 72 cases of phaeochromocytoma-associated Cushing's syndrome (Table S1). In most cases pathology documented ACTH-positive chromaffin tumour along with adrenocortical hyperplasia, while in three cases pathology confirmed the presence of a mixed cortico- ACTH-secreting [39][40][41][42][43][44] CRF-secreting Small 13 Negative Positive Increased Increased Mondello, et al 20 -Positive Increased -Ruggeri, et al 8 Negative Positive Increased -medullary tumour in which corticosteroid production by the tumour per se appeared a more likely aetiology than ectopic ACTH production [29][30][31] ; in three other cases, [32][33][34] the co-presence of adrenocortical adenoma and a phaeochromocytoma was demonstrated. IPSS was undertaken in only five cases and, all cases, confirmed ectopic ACTH secretion.…”
Section: Discussionmentioning
confidence: 94%
“…Literature review revealed 61 papers and 72 cases of phaeochromocytoma-associated Cushing's syndrome (Table S1). In most cases pathology documented ACTH-positive chromaffin tumour along with adrenocortical hyperplasia, while in three cases pathology confirmed the presence of a mixed cortico- ACTH-secreting [39][40][41][42][43][44] CRF-secreting Small 13 Negative Positive Increased Increased Mondello, et al 20 -Positive Increased -Ruggeri, et al 8 Negative Positive Increased -medullary tumour in which corticosteroid production by the tumour per se appeared a more likely aetiology than ectopic ACTH production [29][30][31] ; in three other cases, [32][33][34] the co-presence of adrenocortical adenoma and a phaeochromocytoma was demonstrated. IPSS was undertaken in only five cases and, all cases, confirmed ectopic ACTH secretion.…”
Section: Discussionmentioning
confidence: 94%
“…The anti-ACTH antibodies were strongly positive on immunohistochemistry, suggesting that the preoperative test should have been repeated. Symptoms [11]; [12]; [13]; [14]; [15]; [16]; [17]; [18] IL-6 9 [19]; [20]; [21]; [22]; [23]; [24]; [25]; [26]; [27] PTH 2 [28]; [29] Calcitonin 1 [30] VIP 1 [31] GH 1 [32] Calcitonin ? VIP 2 [33]; [34] ACTH ?…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal regulation and expression of various genes can be induced by dexamethasone in human-derived pheochromocytoma cells (17). Some tumors, for example, can even change phenotype over time from an ACTHproducing non-catecholamine-secreting tumor to a catecholamine-producing pheochromocytoma (18). Pheochromocytomas that secrete massive amounts of catecholamines on exposure to glucocorticoids may thus represent a specific tumor phenotype expressing altered glucocorticoid receptors and secretory patterns.…”
Section: Mechanismsmentioning
confidence: 99%